An Unusual Nodular Tumour of the Penile Shaft with Clinicopathologic and Immunohistochemical Correlation - Poonam Abhay ELHENCE; Deepak VEDANT; Saurabh SINGH; Puneet PAREEK (Türk Patoloji Dergisi, 2022)

(untitled)
Granular cell tumours are uncommon acquired benign tumours of nerve sheath origin that are usually seen in the head and neck region and upper aero-digestive tract. They usually present as solitary small sized nodules in middle age. The tumour is usually benign and composed of sheets of large sized cells with abundant granular cytoplasm containing lysosomal macro-inclusions known as pustulo-ovoid bodies of Milian (POB) that represent the heterogeneity of the lysosomes. No well-established criteria for malignancy have been described for this tumour. In this article, we have discussed a rare case of granular cell tumour of the penis with its characteristic histomorphology and immunohistochemistry and relevant differential diagnosis.